Combating sudden wilt in cucurbits - Chandel, R. S.; Banyal, D. K.; Sharma, B. K.; Verma, K. S. (Indian Horticulture, 2019)
Sudden wilt is emerging as a serious disease on cucurbits, particularly in bottle gourd in low and foothill areas of Himachal Pradesh. The disease is caused by bacteria and transmitted by the cucumber beetles. The feeding beetles spread the wilt pathogens from plant to plant. Symptoms appear at all stages of plant development, but wilting is more severe early in the season when plants are growing rapidly. The most effective disease control is prompt elimination of cucumber beetles either by mechanical barriers or through application of insecticides.